Coupure urbaine et autoroute à péage à Dakar : entre séparation des communautés et contraintes de mobilité ? - Ibrahima Ndiaye (Études Caribéennes)
Southern cities registered from the beginning of 2000s by the implementation of urban projects, which impact positively on the lives of the populations by allowing among other things to reduce the times of traffic, to facilitate the access to the peripheral zones, etc. However, there are very few studies on the impacts of these projects at the crossed areas levels. The objective of this article is to analyze the effects of the division related to the implementation of the toll highway at the local level, by taking as an example the suburb of Dakar. Our methodological approach combines a qualitative approach with the guide of maintenance and a quantitative approach, with the use of the questionnaire. The results of this work show the necessity of establishing a dialogue between different social layers in the implementation of the projects of infrastructure. If the positive effects, in terms of gaining of times and fluidity of the traffic, are clearly perceived on the scale of the urban area, it seems that on a local level, these effects felt by the populations are more negative. Indeed, the facts of not considering of the effects of division are sources of destruction of the social relationship, of losses of autonomy and strengthening of the socio-spatial segregation in the crossed zones.